(untitled) (Global Journal of Human-Social Science, 2024)
The Great Depression was a worldwide economic downturn that began in 1929 and lasted until about 1939. It was the longest and most severe financial crisis ever experienced by the Western World, sparking fundamental changes in economic institutions, macroeconomic policy, and economic theory. Although it originated in the United States, the Great Depression caused drastic declines in output, severe unemployment, and acute deflation in almost every country of the world. The timing and severity of the Great Depression varied substantially across countries. The Depression was particularly long and severe in the United States and Europe however, it was milder in Japan and Latin America. The Great Depression caused enormous hardship for tens of millions of people and the failure of a large fraction of the nation’s banks, businesses, and farms.